Global and local ancestry in African‐Americans: Implications for Alzheimer's disease risk. Issue 3 (16th June 2015) - Hohman, Timothy J.; Cooke‐Bailey, Jessica N.; Reitz, Christiane; Jun, Gyungah; Naj, Adam; Beecham, Gary W.; Liu, Zhi; Carney, Regina M.; Vance, Jeffrey M.; Cuccaro, Michael L.; Rajbhandary, Ruchita; Vardarajan, Badri Narayan; et al.
Abstract: Introduction: African‐American (AA) individuals have a higher risk for late‐onset Alzheimer's disease (LOAD) than Americans of primarily European ancestry (EA). Recently, the largest genome‐wide association study in AAs to date confirmed that six of the Alzheimer's disease (AD)‐related genetic variants originally discovered in EA cohorts are also risk variants in AA; however, the risk attributable to many of the loci (e.g., APOE, ABCA7) differed substantially from previous studies in EA. There likely are risk variants of higher frequency in AAs that have not been discovered. Methods: We performed a comprehensive analysis of genetically determined local and global ancestry in AAs with regard to LOAD status. Results: Compared to controls, LOAD cases showed higher levels of African ancestry, both globally and at several LOAD relevant loci, which explained risk for AD beyond global differences. Discussion: Exploratory post hoc analyses highlight regions with greatest differences in ancestry as potential candidate regions for future genetic analyses.